The Role of Trauma in Early Onset Borderline Personality Disorder: A Biopsychosocial Perspective - Bozzatello, Paola; Rocca, Paola; Baldassarri, Lorenzo; Bosia, Marco; Bellino, Silvio (Frontiers in Psychiatry, 2021)
The role of childhood trauma in the development of borderline personality disorder (BPD) in young age has long been studied. The most accurate theoretical models are multifactorial, taking into account a range of factors, including early trauma, to explain evolutionary pathways of BPD. We reviewed studies published on PubMed in the last 20 years to evaluate whether different types of childhood trauma, like sexual and physical abuse and neglect, increase the risk and shape the clinical picture of BPD. BPD as a sequela of childhood traumas often occurs with multiple comorbidities (e.g. mood, anxiety, obsessive-compulsive, eating, dissociative, addictive, psychotic, and somatoform disorders). In such cases it tends to have a prolonged course, to be severe, and treatment-refractory. In comparison with subjects who suffer from other personality disorders, patients with BPD experience childhood abuse more frequently. Adverse childhood experiences affect different biological systems (HPA axis, neurotransmission mechanisms, endogenous opioid systems, grey matter volume, white matter connectivity), with changes persisting into adulthood. A growing body of evidence is emerging about interaction between genes (e.g. FKBP5 polymorphisms and CRHR2 variants) and environment (physical and sexual abuse, emotional neglect).